METACOGNITIVE REGULATION PROFILES AND ITS POTENTIAL IN DEALING WITH COMPLEX ISSUE - Ihsan Hijria Putra; Hera Novia; Muslim (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
In facing increasingly complex global challenges, metacognitive regulation skills are very important. Metacognitive regulation helps a person in solving the problems they face comprehensively because they can regulate their thinking strategies. This study uses a descriptive approach and uses the MAI (Metacognitive Awareness Inventory) instrument adapted from Schraw and Dennison's work. The researcher involved 37 tenth-grade students from a high school in West Java. The study aimed to map and classify metacognitive regulation skills, with special attention to five main aspects and its potential in dealing with complex issue. Data analysis integrated the Likert scale results with the calculation of the average percentage for each aspect. The research findings revealed varied metacognitive regulation achievements: the Planning aspect reached 81%, Information Management Strategies 73%, Comprehension Monitoring 75%, Debugging Strategy 60%, and Evaluation 76% of the maximum score of 100%. This data indicates that students' metacognitive regulation skills still need development. The study results highlight the importance of developing learning steps that are specifically designed to improve students' metacognitive regulation skills, so that they are better prepared to face complex issues in learning.